ANALISIS IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK (KTR) BERDASARKAN PERDA NOMOR 8 TAHUN 2016 PADA MASA CORONAVIRUS DISEASE-19 DI UPTD PUSKESMAS KABUPATEN ACEH TENGGARA TAHUN 2021 - Husna, Nanda Syahrina (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
COVID-19 outbreak that spread widely until it was declared a pandemic and threatened world health and smoking can worsen the body's immunity, in order to control diseases caused by smoking and exposure to cigarette smoke, the government has issued laws and regulations contained in Law Number 36 of 2009 concerning health in articles 113-115 which regulate Non-Smoking Areas (KTR). The No Smoking Area is a policy with efforts to stop smoking behavior in individuals during the COVID-19 pandemic, therefore it is very important to conduct an analysis through this study. The purpose of this study is to analyze the Implementation of the No Smoking Area Policy (KTR) Based on Regional Regulation Number 8 of 2016 During the CoronaVirus Diseases-19 Period at UPTD PuskesmasThe research method used in this study is a method based on natural object conditions carried out by triangulation (combined) is inductive or qualitative. The informant in this study was the Head of the Community Health Center (Puskesmas) located in 16 sub-districts in Southeast Aceh Regency.This research was carried out by the Puskesmas from December 2021 to May 2022. The results of the study explained that from the Communication Aspect it is still not running effectively, the Human Resources Aspect is still not the formation of a Supervisory team, the Disposition Aspect still has violations and there is no firm sanction only limited to verbal reprimands either in Health Office and Puskesmas, Bureaucratic Aspects only 2 Puskesmas and Health Office have made SK / SOP, while in 15 Puskesmas there is no SK / SOP. There needs to be an evaluation to be carried out based on the Law regulating Non-Smoking Areas (KTR).